Employment and growth in an aging society: A simulation study for Austria - Josef Baumgartner; Helmut Hofer; Serguei Kaniovski; Ulrich Schuh; Thomas Url (Institute for Advanced Studies (IHS), 2004)
In this study we use a long run macroeconomic model for Austria to simulate the effects of aging on employment, output growth, and the solvency of the social security system. By disaggregating the population into six age cohorts and modelling sex specific participation rates for each cohort, we are able to account for the future demographic trends. Apart from a baseline scenario, we perform three alternative simulations that highlight the effects of aging from different perspectives. These include (1) purely demographic developments, (2) increasing labour market imperfections, and (3) higher economic growth due to a productivity shock.
Keywords: C6; E2; O4; 330; economic growth; aging; Austria; Beschäftigungseffekt; Wirtschaftswachstum; Sozialversicherungsfinanzierung; Simulation; Prognose; Österreich; Alternde Bevölkerung